Physical education learning model base on information, communication technology - Widyaningsih, H.; Yulianti, Eva; Setiawan, Iwan (Linguistics and Culture Review, 2021)
There was a revolution in the learning process in schools during the Covid-19 pandemic. At this time, the digital era plays a very important role in replacing human interaction in carrying out all life activities in almost all fields. Currently the teaching and learning process is carried out online. However, for the field of motion learning in physical education, students still have to be able to practice the sports movements that have been arranged in the curriculum. This study aims to determine what learning models are used in providing motion learning materials during this pandemic. Methods: This study used is a survey method with descriptive analysis. The sample in this study were physical education teachers in Junior High Schools in Jakarta. Results: This study showed that the online physical education learning model that is most widely mastered and used in the teaching and learning process. Conclusion: The most widely used media in learning physical education are live youtube and motion learning videos.